Marshall Islands : Disaster Risk Financing and Insurance - World Bank (Washington, DC, 2015)
This note aims to build understanding of the existing disaster risk financing and insurance (DRFI) tools in use in The Marshall Islands and to identify gaps where potential engagement could further develop financial resilience. The likelihood that a hazardous event will have a significant impact on the Marshall Islands has risen with the increasing levels of population and assets in the urban areas of Majuro and Ebeye. The low-lying atolls are at risk of damage to both assets and people as a result of storm surges and tsunamis. The Marshall Islands is expected to incur, on average over the long term, annual losses of US$3 million due to earthquakes and tropical cyclones. In the next 50 years, the Marshall Islands has a 50 percent chance of experiencing a loss exceeding US$53 million. The government takes an ex-ante approach to financing the cost of disasters, but the resources available are limited. The Marshall Islands has a maximum amount of US$15.6 million potentially available in ex-ante instruments to facilitate disaster response. The government s post-disaster budget execution process relies on a variety of financial tools, but the size of the economy limits access to immediate post-disaster cash resources. A number of options for improving disaster risk financing and insurance are presented here for consideration: (a) develop an integrated disaster risk financing and insurance strategy; (b) assess the domestic insurance market for both public and private assets to establish what products are currently offered and to determine their level of uptake; (c) carry out a quantitative analysis to determine whether contingent credit could be an effective tool to access additional liquidity post-disaster; and (d) investigate the possibility of establishing policies for financial assistance to disaster victims in remote communities.